PENCURIAN PRATIMA DALAM KAJIAN HUKUM PIDANA HINDU - Ekasana, I Made Suastika (VYAVAHARA DUTA, 2021)
Pratima Theft Crime is part of the crime of theft or crimes against property or objects that are sacred and sacred or sacred and sanctified which are related to symbols of God, Goddesses, Bhatara-Bhatari and their manifestations. Pratima theft is part of a crime against property as regulated in Book II of the Criminal Code and is also regulated in Hindu Law as Corah or Asteya in Article 6 in conjunction with Articles 336 - 343 Astamo dhyayah Weda Smrti (Manawa Dharmasastra) in conjunction with Articles 51 - 70 Ekodaco dhyayah Weda Smrti (Manawa Dharmasastra). Corah or Asteya is part of Hindu legal norms in the field of Criminal Law or Kantaka Sodhana. The problems studied in the writing are, Are Hindu law norms in the field of Criminal Law included in the national legal system in the Unitary State of the Republic of Indonesia? What are the factors causing the rampant theft of pratima in Bali Province ?. Using the normative legal research method, the conclusion obtained is that the legal norms of Pratima Theft are regulated in the legal system of the Unitary State of the Republic of Indonesia. support each other in the administration of the State. The Pratima Theft legal norms are part of the Criminal Law Norms including one of the Areas of Hindu Law which is one of the recognized religious laws in Indonesia, therefore the Pratima Theft legal norms as one of the religious laws (Hinduism) are automatically included as part of and regulated in the legal system in the Republic of Indonesia. Factors causing pratima theft include human factors, environmental factors, educational factors, social interaction factors and opportunity factors.Keywords: Crime, Theft, Pratima, Hindu Law, Criminal Law.Â